Resonance condition of a microfiber knot resonator immersed in liquids - Lim, Kok Sing; Jasim, Ali Abdulhadi; Damanhuri, Siti Sarah Ahmad; Harun, Sulaiman Wadi; Rahman, Bahanur M. Azizur; Ahmad, Harith (Optical Society of America, 2011)
Effects of immersing a microfiber knot resonator (MKR) in liquid solutions that have refractive indices close to that of silica are experimentally demonstrated and theoretically analyzed. Significant improvement in resonance extinction ratio within 2 to 10 dB was observed. To achieve a better understanding, a qualitative analysis of the coupling ratio and round-trip attenuation of the MKR is performed by using a curve-fitting method. It was observed that the coupling coefficient at the knot region increased when immersed in liquids. However, depending on the initial state of the coupling and the quantity of the increment in the coupling coefficient when immersed in a liquid, it is possible that the MKR may experience a deficit in the coupling parameter due to the sinusoidal relationship with the coupling coefficient.